18th century fresco on the rainbow arch of the former St. Kazimierz’s church at Bernardyńska 15 street in Lublin - Janus, Krzysztof; Janusz, Renata (Budownictwo i Architektura / Civil and Architectural Engineering, 2010)
The paper presents a sacred painting located on the road arch in St. Kazimierz Church in Lublin, which was forgotten for hundreds of years. The fresco was covered by several layers of paints dated from XIX and XX century. It survived likely because the space was too difficult for adaptation as an industry space. The space was used as a storage or a meeting room. Currently it works as a storeroom and a drying room for people living in the building. The present function is utterly incompatible with surrounding work of art you can see on the wall.